Implications of Constitutional Court Decision Number 78/PUU-XXI/2023 on Hoax Law Enforcement in Indonesia in Relation to Article 263 of Law Number 1 of 2023 - Reyraya Respati Paramudhita (Jurnal Iman dan Spiritualitas, 2026)
Constitutional Court Decision Number 78/PUU-XXI/2023 declared Articles 14 and 15 of Law Number 1 of 1946 contrary to the 1945 Constitution and legally non-binding, creating a fundamental legal vacuum (rechtsvacuum) in hoax law enforcement in Indonesia. This normative juridical research, employing statutory and case approaches, analyzes the applicability of Article 263 of the National Criminal Code (Law No. 1 of 2023) as a replacement norm and the multidimensional implications of the Decision on law enforcement. Theoretical frameworks include the Rule of Law (Rechtsstaat) doctrine of Julius Stahl and A.V. Dicey, Gustav Radbruch's Legal Certainty Theory (Rechtssicherheit, Gerechtigkeit, Zweckmäßigkeit), Legal Interpretation Theory (grammatical, systematic, teleological, and constitutional methods), Lawrence M. Friedman's Legal System Theory, and Soerjono Soekanto's five law enforcement factors. The research finds that Article 263 substantially satisfies the lex certa standard required by the Court by explicitly requiring mens rea elements—dolus ("knowingly") and culpa ("reasonably suspected")—along with a tangible harm element of "social unrest," thereby overcoming the three unconstitutional characteristics of the invalidated norm: definitional vagueness, susceptibility to multiple interpretations, and the absence of explicit mens rea. The Decision carries implications across three dimensions: (1) legal substance—elimination of vague "rubber article" norms; (2) legal structure—a paradigm shift from total enforcement to selective full enforcement requiring proof of mens rea; and (3) legal culture—a demand for transformation from forward culture to verification culture. This research recommends drafting implementing regulations to operationally define "social unrest," synchronizing the Court's constitutional interpretation into technical law enforcement guidelines, and strengthening non-criminal mechanisms inspired by Germany's NetzDG as complementary approaches.